EFFECT OF MILLIMETER ELECTROMAGNETIC WAVES ON BUFFER CAPACITY OF ALBUMIN (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
The effect of millimeter range electromagnetic waves (MM EMW) on albumin buffer capacity has been studied. It was shown that MM EMW irradiation of albumin in 0.9% NaCl solution leads to protein buffer capacity change and the direction of this change depends on the irradiation frequency. At the same time the physiological solution, in which the protein is dissolved, does not possess the buffer capacity. At the irradiation of albumin solution by water resonant frequency 51.8 GHz protein buffer capacity increases. At the irradiation by non-resonant frequency for water, 42.2 GHz, albumin buffer capacity decreases.
Keywords: millimeter range electromagnetic waves, irradiation, physiological solution, albumin, buffer capacity